The acute clinical presentation of older patients admitted to the medical wards of Chris Hani Baragwanath Academic Hospital - Mohapi, Makgotso Patience (My University, 2017)
In South Africa, very little is known regarding the spectrum of clinical illnesses for which older patients are admitted to hospital. Within this group who are admitted, even less is known of the burden of HIV disease. This study investigated the clinical indications for acute medical admission in adults over the age of 50 years at Chris Hani Baragwanath Academic Hospital. The study also determined the prevalence of HIV infection of those with HIV, their access and adherence to treatment. Methods: This was a prospective, observational study of patients over 50 years of age who were acutely admitted to the medical wards of Chris Hani Baragwanath Academic Hospital (CHBAH) between August 2014 to March 2015. Results: A total of 200 participants 50 years and older were enrolled, 34% HIV-positive, 37% HIV-negative and 29% whose HIV status was unknown. The HIV-positive group was younger (p <0.0001), had poorer access to pension funds (p<0.0001) and higher burdens of acute infectious illness when compared to their HIV-negative counterparts (p<0.0068). HIV-negative patients had higher rates of acute cardiovascular and haematological conditions (p<0.0001) and higher rates of chronic non-communicable disease (p<0.0004), predominantly diabetes mellitus (p<0.0095) and hypertension (p<0.0024). Conclusion: In older patients hospitalised for acute illness, both infectious and non-communicable disease play a significant role however, in those with HIV, the infectious burden of disease is more prominent while non-communicable chronic disease predominated in those without HIV.
A research report submitted to the faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Internal Medicine. Johannesburg, 2017.
Keywords: Adults Patients; Clinical Illness; HIV